An account of student mentors’ ‘modes of reflexivity’ during an e-mentoring programme at a university - Noorodien-Fataar, Najwa (South African Journal of Higher Education, 2016)
This article focuses on the reflexive deliberations of student mentors during an e-mentoring programme at a South African university. Based on semi -structured interviews and focus group discussions with student mentors, located in a number of different student residences, this article examines how they engage with their learning and use information and communication technology (ICT) and/or social media, such as MXit, Facebook and cellular phones for their learning socialisation. I draw on Margaret Archer’s (2007) concept of ‘modes of reflexivity’ to highlight their ability to navigate their educational and personal circumstances within the university’s context. I show that student mentors’ reflexive stances are essential for understanding the nature of ICT use and their learning engagement in mentoring programmes. The article discusses the reflexive stances of four selected student mentors in relation to their ICT use on a mentoring programme. It discusses the impact of exigent conditions at various sites in the university on their ICT navigations. I show how each of the student mentors establishes viable mentoring platforms in the context of a difficult learning context. The article analyses how each mentor’s reflexive modes informs his or her engagement and interaction with ICTs. The key conclusion of the article is that student mentors tend to adopt similar stances towards their ICT usage, e-mentoring and their own learning. They establish formative relations between their ICT usage and e-mentoring practices on the one hand and their relation to their own learning on the other. The specific nature of each mentor’s reflexive mode explains his or her type of interaction with ICTs and the university’s learning environments more generally.